Attenuation of plasma annexin A1 in human obesity. Issue 1 (4th October 2012) - Kosicka, Anna; Cunliffe, Adam D.; Mackenzie, Richard; Zariwala, M. Gulrez; Perretti, Mauro; Flower, Roderick J.; Renshaw, Derek
Abstract : Obesity‐related metabolic disorders are characterized by mild chronic inflammation, leukocyte infiltration, and tissue fibrosis as a result of adipocytokine production from the expanding white adipose tissue. Annexin A1 (AnxA1) is an endogenous glucocorticoid regulated protein, which modulates systemic anti‐inflammatory processes and, therefore, may be altered with increasing adiposity in humans. Paradoxically, we found that plasma AnxA1 concentrations inversely correlated with BMI, total percentage body fat, and waist‐to‐hip ratio in human subjects. Plasma AnxA1 was also inversely correlated with plasma concentrations of the acute‐phase protein, C‐reactive protein (CRP), and the adipocytokine leptin, suggesting that as systemic inflammation increases, anti‐inflammatory AnxA1 is reduced. In addition, AnxA1 gene expression and protein were significantly up‐regulated during adipogenesis in a human adipocyte cell line compared to vehicle alone, demonstrating for the first time that AnxA1 is expressed and excreted from human adipocytes. These data demonstrate a failure in the endogenous anti‐inflammatory system to respond to increasing systemic inflammation resulting from expanding adipose tissue, a condition strongly linked to the development of type 2 diabetes and cardiovascular disease. These data raise the possibility that a reduction in plasma AnxA1 may contribute to the chronic inflammatory phenotype observed in human obesity.—Kosicka, A., Cunliffe, A. D., Mackenzie, R., Gulrez Zariwala, M., Perretti, M., Flower, R. J., Renshaw, D. Attenuation of plasma annexin A1 in human obesity. FASEB J. 27, 368–378 (2013). www.fasebj.org